The landscape of nature-derived antimalarials-potential of marine natural products in countering the evolving Plasmodium - Prashar, Cherish; Thakur, Narsinh; Chakraborti, Soumyananda; Areeb Hussain, Syed Shah; Vashisht, Kapil; Pandey, Kailash C. (Frontiers in Drug Discovery, 2022)
Malaria poses several challenges to the global research community on both diagnostic and therapeutic fronts. Most prominent of them are deletion of target genes (pfhrp2/3) used in rapid diagnostic tests (RDTs) and the emergence of resistance against frontline antimalarials by the evolving parasite are of utmost importance. Exploration of novel therapeutics for malaria in view of limited vaccine options is a promising resort for malaria control and elimination. The scope of marine-derived chemotherapeutics is exciting, with a significant number of FDA-approved drugs or therapeutic leads under clinical trials for other diseases. This review article discusses the significant antimalarial potential of marine-derived natural products extracted from diverse biota including sponges, bacteria, sea hare and algae etc. Bioassay-guided fractionation of raw extracts from marine organisms for lead identification and further structural characterization of purified compounds compose a sustainable marine-derived drug discovery pipeline; which can be particularly diverted towards the exploration of antimalarials. It is to be noted that the Indian peninsula is largely underexplored, particularly for antimalarials screening; which has a huge marine biodiversity owing to the three distinct water bodies- Bay of Bengal, Indian Ocean and Arabian sea. This review also envisions a collaborative initiative to explore the potential of marine natural products in an economically feasible manner.